1989
DOI: 10.1111/j.1365-2672.1989.tb03397.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrient‐limited growth on pathogenesis‐associated outer membrane proteins of Yersinia enterocolitica

Abstract: From studies based on batch culture, it has been postulated that the expression of the virulence-associated proteins of Yersinia spp. is controlled by temperature and Ca2+, such that these proteins are synthesized only at the higher temperature (37 degrees C) and calcium-scarce conditions of the intracellular environment. It was found, however, that in Yersinia enterocolitica one of these proteins (140 kDa) is not synthesized at submaximal growth rates under any of the relevant conditions, and that another of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Physico-chemical studies on microbial adhesion to surfaces are typically carried out with organisms suspended in buffers to avoid microbial growth or other associated complications (Van Loosdrecht et al ., 1990). In vitro studies have identified changes in antimicrobial efficacy (Evans et al ., 1990, 1991), protein expression (Harakeh & Matin, 1989), cell-surface hydrophobicity (Ljungh & Wad-strӧm, 1995) and adhesion (Fletcher, 1976; Zeng et al ., 1994), depending upon growth conditions. Alternatively, adhesion studies sometimes involve optimal growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Physico-chemical studies on microbial adhesion to surfaces are typically carried out with organisms suspended in buffers to avoid microbial growth or other associated complications (Van Loosdrecht et al ., 1990). In vitro studies have identified changes in antimicrobial efficacy (Evans et al ., 1990, 1991), protein expression (Harakeh & Matin, 1989), cell-surface hydrophobicity (Ljungh & Wad-strӧm, 1995) and adhesion (Fletcher, 1976; Zeng et al ., 1994), depending upon growth conditions. Alternatively, adhesion studies sometimes involve optimal growth conditions.…”
Section: Introductionmentioning
confidence: 99%